Four fools in the age of reason laughter, cruelty, and power in early modern Germany - Outram, Dorinda 1949- (Studies in early modern German history, 2019)
Intro -- Contents -- Acknowledgments -- Introduction -- Chapter One -- Chapter Two -- Chapter Three -- Chapter Four -- Chapter Five -- Conclusion -- Notes -- Bibliography -- Index -- Series